2019
DOI: 10.3122/jabfm.2019.03.180335
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians' Perspectives on Barriers and Enablers of Optimal Prescribing in Patients with Dementia and Coexisting Conditions

Abstract: Patients with dementia experience high rates of polypharmacy, potentially inappropriate medication use, and adverse drug events. There is little guidance for clinicians on how to optimize prescribing for this population. Our objective was to investigate clinician-perceived barriers to and facilitators of optimizing prescribing for people with dementia. Methods: Qualitative study involving semistructured interviews of primary care and specialist clinicians in urban, suburban, and rural settings. Transcripts wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(70 citation statements)
references
References 41 publications
1
69
0
Order By: Relevance
“…' 39 Studies described a trend towards the prescribing of medication for asymptomatic patients to prevent future morbidity and mortality, 40 and a continuation of unnecessary preventive medicine in older patients. 41,42 There was a lack of financial incentives for primary healthcare practitioners to address polypharmacy: Patients in some countries with free prescriptions (or discount cards for the costs of medications) were less likely to cease medications. 44…”
Section: Cultural Barriersmentioning
confidence: 99%
See 2 more Smart Citations
“…' 39 Studies described a trend towards the prescribing of medication for asymptomatic patients to prevent future morbidity and mortality, 40 and a continuation of unnecessary preventive medicine in older patients. 41,42 There was a lack of financial incentives for primary healthcare practitioners to address polypharmacy: Patients in some countries with free prescriptions (or discount cards for the costs of medications) were less likely to cease medications. 44…”
Section: Cultural Barriersmentioning
confidence: 99%
“…60 Opportunities for deprescribing were sometimes lost due to GPs' lack of direct contact with patients who receive repeat prescriptions. 57,61 GPs were reluctant to stop a medication started by another specialist in a different healthcare setting: 41,51,56 'GPs outlined challenges in terms of professional boundaries with hospital prescribers and some GPs were reportedly unwilling to challenge recommendations from secondary care ... ' 43 Uncertainties gave rise to GPs' fears over adverse effects from stopping medications, legal repercussions, and of being perceived by their patients as disengaging or not caring about them if they broached the subject of stopping medications. 41,42,47,50,56,62…”
Section: Organisational Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, they may not recognize that the patient's ED visit or hospitalization could have been due to an anticholinergicinduced adverse event. In addition, clinicians are often hesitant to discontinue medications that are being prescribed by other providers involved in the patient's care [38], or they may have incomplete information about patient drug regimens, particularly after patients transition from the hospital to the outpatient setting. For example, a previous study that found that 96% of primary-care provider medication lists contained discrepancies compared with what the patient was actually taking [39].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a previous study that found that 96% of primary-care provider medication lists contained discrepancies compared with what the patient was actually taking [39]. This problem may be magnified for patients with dementia, who are often unable to give clear medication histories and may not attend visits with caregivers who are knowledgeable about their drug regimens [38]. Clinicians may also assume that serious falls and delirium are unavoidable consequences of dementia and may not connect these events to medications.…”
Section: Discussionmentioning
confidence: 99%